ANALISIS EFEKTIVITAS IKLAN TELEVISI PRODUK AQUA DENGAN MENGGUNAKAN METODE EPIC MODEL DAN PENGARUHNYA TERHADAP KEPUTUSAN PEMBELIAN PRODUK AQUA DI KOTA MANADO - Sumampouw, ANGELIA (Universitas Sam Ratulangi, 2013)
Advertising is a means to promote goods or services who want to offer, especially to the community. For most companies, advertising is becoming an attractive option, as well as a source of information, the ad also viewed as entertainment media and effective marketing communications media to reach target market especially if aired on television. One of the companies that make brand building through advertising is PT. Aqua Golden Mississippi. The purpose of this study was to determine the effectiveness of television advertising a product model using the method of Aqua EPIC and its effects on Product purchasing decisions and simultaneous partial Aqua. Methods of analysis used in this study is a method of EPIC model and multiple regression analysis. Results of the analysis using the method of the EPIC model in mind that television advertising has been effective in Aqua product introduce product Aqua to the consumer. And in the Multiple Linear regression Method becomes Y =-2,344 0, 167X1 0, 065X2 0, 084X3 0, 087X4.. the four variables that are used give the same effect that a positive effect on purchasing decisions. The numbers R Square is called the coefficient of determination, the result was 70,2% consumer purchase decisions are influenced by variables emphaty, persuasion, impact, and communicatio whereas 29,8% explained by other variables outside of the variables used in the study. Â Keywords : empathy, persuasion, impact, communication and purchasing decisions